Assessing Numeracy Skills Among Indonesian Students: A Comparative Study of Gender, Regional Disparities, and Study Habits - Amelia, Della; Arwan, Juwintar Febriani (PEDAGOGIA, 2024)
Numeracy is a critical skill that underpins a wide range of cognitive and practical abilities such as logical reasoning, problem-solving, and the capacity to analyze and interpret data. How students eventually grasp this skill is influenced by a complex interplay of factors that include gender, area of residence, and study habits. Through a comparative study, this research aimed to compare students’ numeracy skills according to certain categories, such as students’ gender, area of living, as well as study habits. A total of 506 randomly selected secondary school students (Female = 285; Male = 221) participated in this study. To collect the data, an online survey was administered to targeted students with a total of 56 questions in the form of structured questionnaire. Through both descriptive and inferential analysis this study revealed that in terms of gender female students outperformed male counterpart with significant statical difference. Moreover, students who live in urban areas had the highest numeracy skills compared to other areas. Lastly, students who set pre-lesson preparation and post-lesson review displayed significantly higher numeracy skill compared to those who are not. Elaboration for each finding further discussed in this paper.